ENFORCEMENT OF LAW AGAINST OF SMUGGLING IMPORTED USED CLOTHING ACCORDING TO POSITIVE LAW IN INDONESIAN - RIDWAN, SALWA BILLA MIRZA (Jurnal Penegakan Hukum dan Keadilan, 2024)
Background: The smuggling of imported used clothing has become a significant problem in Indonesia, causing various negative impacts on the domestic economy and society. Law enforcement against this smuggling is important to protect the domestic apparel industry and ensure fairness in international trade.Research Methods: This research uses an analytical descriptive approach by collecting data from various legal sources, including legislation, court decisions, and related literature. Analysis was conducted to understand the legal framework relating to law enforcement against smuggling of imported used clothing in Indonesia.Discussion: The results of the analysis show that there is a sufficient legal framework to address the issue of smuggling of imported second-hand clothing in Indonesia. However, the main challenge lies in effective implementation and enforcement. Better coordination between law enforcement agencies and other relevant parties is needed, as well as increased public awareness on the importance of avoiding illegally obtained products.Conclusion: Enforcing the law against smuggling of imported used clothing in Indonesia is an important step to protect local industries and maintain fairness in international trade. Greater efforts are needed from the government, law enforcement agencies, and society as a whole to address this challenge and ensure compliance with applicable laws.